Europe and the other: Non-European concepts of civil society - Hinnerk Bruhns; Dieter Gosewinkel (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2005)
The idea and contributions of this collection of articles on “Non-European concepts of civil society” originate from a European research project. The European Civil Society Network (CiSoNet) deals with a highly important aspect of European integration and enlargement, namely, the emergence, dynamics, and perspectives of a European-wide civil society. Ci- SoNet is embedded in the EC's 5th Framework Programme's Key Action on “Improving the socio-economic knowledge base”, spanning a period of work from 2003 to 2005. Its aim is to stimulate cross-disciplinary research concentrating on transnational dimensions of civil society, and thereby to contribute to the establishment of a European research area within the social sciences and the humanities.
Keywords: 300